The entrepreneurial revolution in science research and education - M. Halma (Mukachevo State University, 2024)
There are significant challenges in both student and researcher engagement in both education and research, and one contributing factor is the lack of autonomy that each person experiences. This work charts a new path, whereby students and researchers are free to pursue their own interests, and the role of the teacher or university is to support and guide them. This article is a narrative review examined the challenges faced by the educational industry and how they can be remedied through student led, entrepreneurial education, which can take place online. This article examines the impacts of learner autonomy and present alternative apprenticeship models which can be performed inexpensively and produce value independent of the education itself. Apprenticeship, self-directed and project-based pedagogy provides pupils with the skills that they need to succeed in the modern world, differing importantly from standard education, where the relevance to employers is decreasing. While currently, scientific institutions face a crisis of innovation and a related crisis of public trust, entrepreneurial education provides a means of addressing these related problems. These changes have implications at the institutional level, as well as for the relationship between science and society. During budgetary crises, these changes present ways to provide an improved educational experience at lower cost. Overall, entrepreneurial education may be an effective and cost-effective way to perform research and to train pupils for the skills needed in the 21st century. The work provides a roadmap to how existing educational institutions can adapt to the sea change underway with online education, as well as advise new entrants on best practices